The implicit processing of categorical and dimensional strategies: an fMRI study of facial emotion perception - Matsuda, Yoshi-Taka; Fujimura, Tomomi; Katahira, Kentaro; Okada, Masato; Ueno, Kenichi; Cheng, Kang; Okanoya, Kazuo (Frontiers in Human Neuroscience, 2013)
Our understanding of facial emotion perception has been dominated by two seemingly opposing theories: the categorical and dimensional theories. However, we have recently demonstrated that hybrid processing involving both categorical and dimensional perception can be induced in an implicit manner (Fujimura etal., 2012). The underlying neural mechanisms of this hybrid processing remain unknown. In this study, we tested the hypothesis that separate neural loci might intrinsically encode categorical and dimensional processing functions that serve as a basis for hybrid processing. We used functional magnetic resonance imaging to measure neural correlates while subjects passively viewed emotional faces and performed tasks that were unrelated to facial emotion processing. Activity in the right fusiform face area (FFA) increased in response to psychologically obvious emotions and decreased in response to ambiguous expressions, demonstrating the role of the FFA in categorical processing. The amygdala, insula and medial prefrontal cortex exhibited evidence of dimensional (linear) processing that correlated with physical changes in the emotional face stimuli. The occipital face area and superior temporal sulcus did not respond to these changes in the presented stimuli. Our results indicated that distinct neural loci process the physical and psychological aspects of facial emotion perception in a region-specific and implicit manner.